Colombia : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1995)
This paper reviews economic developments in Colombia during 1990-95. In 1990-94, Colombia built upon the structural reforms initiated in the mid-1980s. The administration achieved its objective for output but not for inflation. Real GDP growth averaged 4.0 percent in 1990-94 and reached an estimated 5.3 percent in 1994. The rate of unemployment fell from 11 percent in early 1989 to 7.4 percent by the third quarter of 1994. Private savings declined from 15 percent of GDP in 1991 to an estimated 6 percent in 1994.